Efektivitas Ultrasound Therapy Terhadap Penurunan Nyeri Pada Pasien Carpal Tunnel Syndrome: Literatur Review - Novia Fitri Aliim; Dini Nur Alpiah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Carpal tunnel syndrome (CTS) is a muscle and bone disorder caused by pressure on the median nerve in the carpal tunnel area. Decreased hand function, pain, and numbness are common symptoms. A PICO literature review of randomized controlled trials (RCTs) published between 2021 and 2025 was used to determine the effectiveness of ultrasound therapy in reducing pain and improving hand function in CTS patients. Ten international journals were eligible for the study. The results showed that, compared with other treatment methods, ultrasound therapy, both ultrasound-assisted and conventional, reduced pain and improved hand function. These results suggest that ultrasound therapy is an effective physiotherapy method for CTS patients.